The spatial dynamics of financial activities in Beijing: agglomeration economies and urban planning. Issue 6 (2nd July 2020) - Pan, Fenghua; Hall, Sarah; Zhang, Hua
ABSTRACT: Beijing is widely recognized as the leading political, cultural, education and innovation center in China. However, its role as a financial center in national and international financial landscapes is less well understood. In response, this paper specifies the development and change of Beijing as an international financial canter by focusing on the geographies of financial activities within the city. Over the last two decades, financial activities have grown rapidly in Beijing and become more geographically concentrated. Two key financial districts are developing in Beijing: one in Financial Street and one in the Central Business District. The paper argues that the spatial patterns of financial activities in Beijing have been driven by both market and state forces. Drawing on the findings of a regression analysis, the paper reveals the role of municipal policy and planning alongside agglomeration economies in shaping the financial geographies of international financial centers.